The impact of the COVID-19 pandemic on the rehabilitation therapy of children and adolescents with cerebral palsy: a nationwide, health insurance data-based study - Shin, Jieun; Hong, Mi Jin; Park, Jong Bum; Lee, Yung Jin (Frontiers in Public Health, 2024)
The coronavirus disease 2019 (COVID-19) pandemic has profoundly affected the utilization of rehabilitation services. Existing evidence investigating this issue at the nationwide level is lacking, and it is uncertain whether the effects of the COVID-19 pandemic on the use of rehabilitation therapy of children and adolescents with cerebral palsy. This study aimed to investigate the impact of COVID-19 on the rehabilitation therapy of children and adolescents with cerebral palsy. Methods: We obtained data from South Korea's Health Insurance Review and Assessment Agency for 2017-2021. By analyzing the claims data, we focused on rehabilitation therapy in individuals with CP under 18 years of age. We categorized these according to therapy type (physical, occupational, or dysphagia), medical facility, hospital visits, and insurance. We calculated the patient counts and average claims per person and compared the average from before to during the COVID-19 pandemic. Results: Over the 5 years, there was a significant decline in the number of patients undergoing rehabilitation therapy (trend P = 0.004), but the average claims per person remained stable (trend P = 0.971). During the COVID-19 pandemic, the average number of claims per person decreased significantly compared to the control period (P = 0.013). Both the physical (P = 0.049) and occupational therapy groups (P = 0.019) showed significant differences in claims. General hospitals and hospitals experienced a decrease in average cases by 2.2 (P < 0.001) and 2.4 (P < 0.001) respectively, while long-term care hospitals increased by 3.1 cases (P < 0.001). Outpatients showed a decline of 2.0 cases (P < 0.001), whereas inpatients showed an increase of 5.9 cases (P < 0.001). Individuals with health insurance decreased by 0.5 cases (P = 0.007), but the decrease of 0.08 cases among medical aid-covered individuals was not statistically significant (P = 0.898). Conclusions: In 2020-2021, the average number of claims per person showed a significant decrease compared to the pre-COVID-19 pandemic period (2017)(2018)(2019). Depending on the type of treatment, the number of claims for physical and occupational therapy significantly decreased.